Serenade to mon coeur / Stefanie Natasha Rich Joseph - Joseph, Stefanie Natasha Rich (Universiti Teknologi MARA Cawangan Kedah, 2022)
A compilation of poems from interested 118 lecturers and academicians from UiTM and other higher learning institutions.